Implementasi Pendekataan Instruksional dan Pendekataan Proses Kelompok dalam Manajemen Kelas pada Pembelajaran Ilmu Pengetahuan Sosial (IPS) - Wafiq Azizah Hasibuan; Nabila Zhaskia; Shela Andini; Hafizah Aulia; Dahliana Dahliana; Junaldi Putra; Ade Irma (Madrasah: Jurnal Pendidikan Madrasah, 2026)
Classroom management is one of the key factors determining the success of the teaching and learning process. Teachers are expected to create a conducive learning environment by employing approaches that are aligned with students' characteristics. This study aimed to describe the implementation of the instructional approach and the group process approach in classroom management at a public junior high school in Kampar Regency. The study employed a descriptive qualitative method, with data collected through classroom observations, interviews, and document analysis. The research participants consisted of teachers. The findings indicate that the instructional approach was implemented through systematic instructional planning, structured content delivery, the use of diverse teaching methods, and the provision of learning motivation to students. Meanwhile, the group process approach was implemented through group-based learning, classroom discussions, presentations, and collaborative activities in completing learning tasks. Both approaches were found to create a more active learning environment, enhance students' participation, and assist teachers in managing classrooms effectively. Nevertheless, several challenges were identified, including differences in students' academic abilities and limited time available for implementing group activities. Therefore, teachers need to demonstrate creativity in integrating these two approaches to optimize the achievement of learning objectives.